Clinical and Laboratory Characteristics of Acute Carditis and the Role of Risk Factors in their Development - Atoyeva Munisxon Nabiyevna (American Journal of Bioscience and Clinical Integrity, 2024)
The true prevalence of carditis in the pediatric population is not known. The lack of clear diagnostic criteria, as well as the high prevalence of infectious diseases in children and, in particular, respiratory viral, leads to a fairly frequent involvement in the pathological process of the cardiovascular system. An important role in the development of acute carditis in young children is played by an unfavorable perinatal history, protein–energy eating disorder and a high tendency to hyperergic reactions.